2022
DOI: 10.1021/acs.jafc.2c06171
|View full text |Cite
|
Sign up to set email alerts
|

L-Theanine Modulates Intestine-Specific Immunity by Regulating the Differentiation of CD4+ T Cells in Ovalbumin-Sensitized Mice

Abstract: Ovalbumin (OVA), a common food protein, can cause deadly allergies with intestine-specific immune reactions. L-Theanine (LTA) shows great potential for regulating intestinal immunity. To investigate the regulatory effect of LTA intervention on intestine-specific immunity, a 41 day experiment was performed on BALB/c OVA-sensitized mice. The results show that injecting female mice intraperitoneally with 50 μg of OVA and administering 30 mg of OVA 4 times can successfully establish an OVAsensitized mouse model. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…According to the conversion coefficient (0.11) of the dosage of mice (20 g) converted to humans (60 kg), the LTA + EGCG dosages used in this study (20 mg kg −1 LTA + 80 mg kg −1 EGCG) could be extrapolated to human dosages (0.22 g per 60 kg green tea), providing a basis for the subsequent development of LTA and EGCG as a functional food. 49…”
Section: Discussionmentioning
confidence: 99%
“…According to the conversion coefficient (0.11) of the dosage of mice (20 g) converted to humans (60 kg), the LTA + EGCG dosages used in this study (20 mg kg −1 LTA + 80 mg kg −1 EGCG) could be extrapolated to human dosages (0.22 g per 60 kg green tea), providing a basis for the subsequent development of LTA and EGCG as a functional food. 49…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation criteria of jejunum damage were performed according to our previous study. 17 Biochemical index measurements. Glucose levels were determined with a blood glucose meter (Roche, Shanghai, China) after overnight fasting.…”
Section: Papermentioning
confidence: 99%
“…However, this was achieved by the anti-oxidation activity. l -Theanine (LTA), the most abundant non-protein amino acid (AA) in tea, is a structural analogue of glutamine, and shows multiple biological activities such as immunomodulation 17 and enhancing cognition. 18 Besides, LTA is effective in regulating nutrient metabolism in normal and stressed organisms.…”
Section: Introductionmentioning
confidence: 99%
“…54 Although supplementation with FO for 14 days did not markedly change the ratio of CD 4+ / CD 8+ , it enriched the CD 4+ T cell numbers in the colon, which secretes immune cytokines IL-10, IFN-γ, and IL-4. 55,56 All of these indicated that acute Vp infection induced a higher abundance of CD 3+ T cells and activated proinflammatory response, whereas presupplementation with 4 mg of FO promoted immune modulation by enhancing CD 4+ T cell proliferation, which in turn increased anti-inflammatory cytokine IL-4 and IFN-γ levels to alleviate Vp-induced inflammation disorder in the gut.…”
Section: ■ Discussionmentioning
confidence: 99%